1999
DOI: 10.1021/jp991481f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Migration in the Phenylethen-2-yl Radical

Abstract: The migration of hydrogen in the phenylethen-2-yl radical is investigated by determining optimal geometries and barrier and reaction energies using several quantum mechanical methods. Rate coefficients and equilibrium constants are obtained using the calculated data and RRKM theory. Theoretical methods compared include PM3, MP2, B3-LYP, CASPT2, and G2MP2. The applicability of these methods and comparisons with two others, G2M and CBS-RAD proposed to improve treatment of radicals, are discussed. The results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
5
38
0
Order By: Relevance
“…However, the prediction of the equilibrium twist angle of the nonplanar molecule is strongly dependent on the level of theory considered for the computation. With second-order perturbation theory (MP2), Moriarty et al 21 found an equilibrium twist angle of 27.6°with a small basis set (6-31G(d)), while we obtained 18.8°w…”
Section: Torsional Potentialmentioning
confidence: 52%
See 1 more Smart Citation
“…However, the prediction of the equilibrium twist angle of the nonplanar molecule is strongly dependent on the level of theory considered for the computation. With second-order perturbation theory (MP2), Moriarty et al 21 found an equilibrium twist angle of 27.6°with a small basis set (6-31G(d)), while we obtained 18.8°w…”
Section: Torsional Potentialmentioning
confidence: 52%
“…Once again, it appears that the twist angle is a function of the size of the basis set. Moriarty et al 21 optimized the geometric structures of 2-phenylvinyl and 1-vinyl-2-phenyl at several levels of theory and with different basis sets. Using small basis sets (from 3-21G to 6-31G(d,p)), they found smaller equilibrium twist angles for the two molecules than the present MP2 calculations: 38.1°for 2-phenylvinyl and 5.8°for 1-vinyl-2-phenyl with their highest level of theory (MP2/6-31G(d,p)).…”
Section: Torsional Potentialmentioning
confidence: 99%
“…Such analysis [61,62] was carried out by Frenklach and co-workers (see Table 1.2 and Figure 1.7). The overall process, whose key intermediate steps involve hydrogen migration, well investigated reactions in the soot formation literature [63], is thermodynamically favorable (Table 1.2): Semiempirical PM3-level quantum chemistry analysis yielded −71 kcal/mol as the enthalpy of the overall reaction C 12 H 7 + C 2 H 2 = C 14 H 9 (Figure 1.7). Our own higher-level density functional theory calculations were in good agreement with such analysis in both qualitative and quantitative terms.…”
Section: 2 Heats Of Reaction Calculated For a Prototypical Process Omentioning
confidence: 99%
“…Geometry optimizations were performed with the B3LYP hybrid functional [27] and the 6- [16,28,29]. The energies of transition states predicted by this method, however, are often underestimated by about 5 kcal mol -1 [30,31].…”
Section: Energeticsmentioning
confidence: 99%
“…The initial surface HACA model was based on the armchair edges of aromatics [13], yet more recent work [14][15][16][17][18] has explored growth on zigzag edges, which can be formed by the filling of armchair edge boat sites. A gaseous acetylene molecule can adsorb onto an H-activated zigzag edge (i.e., add to a surface radical formed by H abstraction) and then react to form a fivemembered, cyclopenta edge ring.…”
Section: Introductionmentioning
confidence: 99%